STRUCTURAL FEATURES OF 2-(4,5-DIPHENYL-4H-1,2,4-TRIAZOL-3-YL)THIO)-1-(3-METHYL-3-PHENYLCYCLOBUTYL)ETHANONE : X-RAY DIFFRACTION AND DFT CALCULATIONS - Sen, Fatih; Yilmaz, Ibrahim; Dincer, Muharrem; Cukurovali, Alaaddin (Soc Chilena Quimica, 2015)
This paper reported that the combined X-ray diffraction and DFT computational study on molecular structure of the title compound, [C27H25N3O2S]. The compound contains a cyclobutane, a triazole and three phenyl rings. The molecular geometry of the compound was brought to light by X-ray single crystal structure determination. X-ray study shows that the title compound has a weak intermolecular C-O center dot center dot center dot pi interaction as well as many D-H center dot center dot center dot pi and D-H center dot center dot center dot pi hydrogen bonds. The initial guess on the compound was first obtained from the X-ray coordinates which were optimized by Density Functional Theory (DFT)/B3LYP method with 6-31G(d, p) and 6-31G+(d, p) as basis sets. DFT electronic structures were compared to the experimentally determined molecular structure in the solid state.
Keywords: Spectroscopic Characterization